Sensory and instrumental textural changes in fillets from Pacú (Piaractus mesopotamicus) fed different diets - Pavón, Yanina Lorena (2018)
The influence of two dietary treatments on quality properties, like textural parameters, sensory profile, and nutritional composition of Pacú fillets (Piaractus mesopotamicus) were studied. Pacú were fed diets based on plant-meals containing 13 g 100 g−1 fish meal (FMD) or bovine plasma protein concentrate (BPPD) as a complete replacement of fish meal. Harvested fish were filleted, kept frozen at −20C for 7 days before analysis. Chemical composition, amino acid and fatty acid profiles, and CIE-Lab parameters of fillets were measured. Sensory characteristics and texture profile analysis (TPA) were conducted for cooked portions. Average values of TPA hardness, chewiness, and deformability modulus were higher in BPPD samples but there was no significant difference in cohesiveness between samples. In accordance with TPA, higher values of firmness and chewiness as well as less flaky muscle were detected in BPPD samples by sensory panel. However, there was no significant difference in the characteristics associated with higher freshness between samples. Total color difference was lower in BPPD samples. Differences in protein, lipid, ash, and moisture content of FMD or BPPD fillets were not found (p >.05). BPPD fillets showed higher basic and sulfur amino acids. Saturated and polyunsaturated fatty acid contents were higher in FMD fillets than BPPD. However, a significantly higher n−6/n−3 ratio for FMD fillets was observed. The higher values of textural parameters observed for BPPD cooked fillets and the lower n−6/n−3 ratio imply a better sensory and nutritional quality of fillets from fish fed with BPPD. Practical applications: A complete study is presented on how the source of protein and lipids in feed affect both the sensory profile and the nutritional composition of fillets of Pacú (omnivorous temperate freshwater fish) cultivated in the second stage of fattening. Instrumental texture analysis of the fillets is presented, identifying the indicators that match with sensorial analysis. This analysis can help the industry of aquaculture in the evaluation of new ingredients or diets for fish feeding with impact in the quality of fillets.